IMPACT OF HALAL LABELIZATION, CONSUMER AWARENESS AND BEHAVIOR INTENTION TOWARDS FAST FOOD BUYING DECISION - Cahya, Bayu Tri; Sufiana, Fika; Islamiah, Makrufah Hidayah (State Institute of Islamic Studies (IAIN) Palu, 2020)
Fast food is one type of food that is prepared and served quickly. In this research, the writer wants to know whether halal labeling, consumer awareness and behavioral intention influences fast food buying decisions. This research used quantitative method. The data in this study are primary data. Technique of determining the sample using proportional random sampling technique with a sample size is 83 students from Islamic Economics and Business Faculty IAIN Kudus Sharia Economics Major in class of 2015 and 2016. Data analysis techniques using linear regression analysis. The findings indicate that the variable halal labeling has significant influence on fast food buying decision, consumer awareness variable have significantly influenced the fast food buying decision and variable behavior intention has no effect which is not significant to the fast food buying decision. Keywords: Halal labeling, consumer awaereness, behavior intention, buying decisions.